Pamidronate Disodium for Palliative Therapy of Feline Bone-Invasive Tumors. (9th June 2014) - Wypij, Jackie M.; Heller, David A.
Abstract : This study sought to quantify in vitro antiproliferative effects of pamidronate in feline cancer cells and assess feasibility of use of pamidronate in cats by assessing short-term toxicity and dosing schedule in cats with bone-invasive cancer. A retrospective pilot study included eight cats with bone invasive cancer treated with intravenous pamidronate. In vitro, pamidronate reduced proliferation in feline cancer cells (P < 0.05 ). One cat treated with pamidronate in combination with chemotherapy and two cats treated with pamidronate as a single agent after failing prior therapy had subjective clinically stable disease; median progression free interval in these cats from initial pamidronate treatment was 81 days. Three cats developed azotemia while undergoing various treatment modalities including nonsteroidal anti-inflammatory drugs and pamidronate. Median overall survival was 116.5 days for all cats and 170 days for cats with oral squamous cell carcinoma. Median progression free survival was 55 days for all cats and 71 days for cats with oral squamous cell carcinoma. Pamidronate therapy appears feasible for administration in cancer bearing cats with aggressive bone lesions in the dose range of 1-2 mg/kg every 21–28 days for multiple treatments. No acute or short-term toxicity was directly attributable to pamidronate.